The Long-Run Effects of College Remedial Education - Marco Alberto De Benedetto; Maria De Paola; Vincenzo Scoppa; Janna Smirnova (Institute of Labor Economics (IZA), 2022)
We investigate the long-run impact of college remedial education on students' academic performance and employment status. By implementing a Fuzzy Regression Discontinuity Design we show that attending remedial courses positively affects the probability to get a university degree, whereas no significant effect is found on labour market outcomes.
Keywords: I23; I28; C26; 330; remediation; education; employment; RDD